Effects of mulch location on banana weevil, nutrients, soil water, and biomass in banana - McIntyre, B.D.; Gold, Cliford S.; Ssali, H.; Riha, S.J. (Springer, 2003)
Major constraints to banana (Musa spp., genome group AAA) production, a dietary staple for over 70 million people in sub-Saharan Africa, are pest infestations, poor nutrition and inadequate water. Although mulch can improve soil water and nutrient status, many farmers believe it also promotes the proliferation of banana weevil (Cosmopolites sordidus), one of the most serious banana pests. In this study, we evaluated the effects of mulch location (mulch to base of banana pseudostem; mulch recessed 1 m from the pseudostem) on banana weevil, soil and plant nutrient status, soil water, and banana growth and development. After 3 years, the fully mulched plots had significantly more soil Ca and Mg than plots that did not receive mulch. Banana foliar K concentration was significantly higher in both mulch treatments (full and recessed) than in the control (no mulch) plots. The mulched plots had greater recharge after rainfall events and higher soil water contents during dry periods due to increased infiltration in the mulched plots. However, the mulched plots also exhibited significantly higher banana weevil densities and greater plant damage than the control plots. There was no difference in weevil damage with mulch location, although weevil density was higher in the fully mulched plots throughout most of the trial. Despite greater weevil damage, the treatments that were mulched yielded significantly heavier bunches. Hence the effects of the mulch on soil water infiltration and banana foliar nutrient status outweighed the detrimental effects of banana weevil damage.